Backpack - Herrera, Mario (Pearson Education, cop, 2005)
This 7-level course focuses on getting young learners to enjoy communicating in English and takes a highly integrated approach to developing grammar, vocabulary and all four language skills. There is a lively mix of illustrations, photography, chants, songs, games, TPR and project work